Genetic conflict outweighs heterogametic incompatibility in the mouse hybrid zone? - Macholán, Milos; Baird, Stuart J E; Munclinger, Pavel; Dufková, Petra; Bímová, Barbora; Piálek, Jaroslav (BMC evolutionary biology, 2008)
BACKGROUND: The Mus musculus musculus/M. m. domesticus contact zone in Europe is characterised by sharp frequency discontinuities for sex chromosome markers at the centre of wider clines in allozyme frequencies. RESULTS: We identify a triangular area (approximately 330 km2) where the musculus Y chromosome introgresses across this front for up to 22 km into domesticus territory. Introgression of the Y chromosome is accompanied by a perturbation of the census sex ratio: the sex ratio is significantly female biased in musculus localities and domesticus localities lacking Y chromosome introgression. In contrast, where the musculus Y is detected in domesticus localities, the sex ratio is close to parity, and significantly different from both classes of female biased localities. The geographic position of an abrupt cline in an X chromosome marker, and autosomal clines centred on the same position, seem unaffected by the musculus Y introgression. CONCLUSION: We conclude that sex ratio distortion is playing a role in the geographic separation of speciation genes in this section of the mouse hybrid zone. We suggest that clines for genes involved in sex-ratio distortion have escaped from the centre of the mouse hybrid zone, causing a decay in the barrier to gene flow between the two house mouse taxa.
Keywords: alely; zeměpis; vznik druhů (genetika); tok genů; populační genetika; Algorithms; Hybridization, Genetic; chromozom Y; Likelihood Functions; Geography; Genetics, Population; genetické markery; Female; Gene Flow; Alleles; zvířata; Europe; myši; hybridizace genetická; Sex Ratio; Mice; ženské pohlaví; Male; modely genetické; Genetic Markers; algoritmy; Genetic Speciation; pravděpodobnostní funkce; Models, Genetic; poměr pohlaví; Animals; mužské pohlaví; Y Chromosome; Evropa